Marine Insurance System - Noprianto, Windi; Komalasari, Yeti (IWTJ : International Water Transport Journal, 2020)
Losses that arise due to the risk of transporting goods are losses that are often insured as insurance for the transportation of goods, whether carried out by land, sea and air transportation. Various losses may arise from the risk of transporting goods, becoming the object of transportation insurance. Specifically, risks are the possibility of an unwanted event that results in a loss in a certain period of time. The possibility of loss of goods in carrying out the transportation of goods as an object of transportation of goods insurance, cannot be separated from the existence of cause and effect as one of the principles in the agreement including insurance as a special form of agreement that the insurer will provide compensation to the insured due to a loss,